Konsep dan Penerapan Model Kebijakan Corporate Environmental Responsibility di Indonesia - Syamsudin Isnaini; Amalia Diamantina (Fakultas Hukum Universitas Bangka Belitung, 2020)
The friction between economic interests and environmental interests has become a serious problem today. The friction between the two interests is evident in the activities of a company, therefore a company is given responsibility for the impact caused by its activities. This responsibility is â€œcorporate social and environmental responsibilityâ€. However, the term